Smooth Particle Hydrodynamics-Based Characteristics of a Shaped Jet from Different Materials - Yin, J.P.; Shi, Z.X.; Chen, J.; Chang, B.H.; Yi, J.Y. (Проблемы прочности, 2019)
The liner material is one of the key factors in the design of armor-piercing ammunition that effect the penetration efficiency. The performance of a shaped jet formed by the charge liner is determined by different properties of the material under the blasting action, in particular for the target with explosive reactive armor, which diminishes the penetration power by dispersing the shaped jet. The performance of shaped jet elements from different materials is studied, AUTODYN finite element software and smooth particle hydrodynamics method are employed to simulate the formation of shaped jet elements from the three materials: Cu, PTFE, and PTFE/Cu and their penetration into target plates, which was verified in the experiment. A shaped jet for a Cu liner is shown to be formed under the action of a detonation wave, while PTFE and PTFE/Cu materials generate a dispersive particle jet. The head velocity of a Cu jet is found to be the lowest, the penetration depth is the deepest, and the penetration hole size is the smallest; the velocity of a PTFE particle jet is the highest and the penetration depth is the shallowest, the penetration hole size takes the mid-position; the head velocity and penetration depth of a PTFE/Cu jet take the mid-position, while the penetration hole is the largest. The PTFE/Cu jet possesses higher penetration performance as compared to the PTFE jet, and its hole-opening capability is improved as compared to the Cu jet. Облицовочный материал один из ключевых факторов при создании бронебойных боеприпасов, оказывающий влияние на эффективность внедрения. Работоспособность кумулятивного заряда, формируемого его облицовкой, определяется различными свойствами материала в условиях взрывной нагрузки, в частности для мишени с элементами динамической защиты, которые уменьшают проникающую способность, рассеивая кумулятивный заряд. Изучены рабочие характеристики элементов кумулятивного заряда из различных материалов. Конечноэлементное программное обеспечение AUTODYN и метод гидродинамики гладких частиц используются при моделировании формирования этих элементов и их внедрении в пластинымишени из трех материалов: Cu, ПТФЭ и ПТФЭ/Сu, что было проверено экспериментально. Показано, что кумулятивный заряд для медной облицовки формируется под действием детонационной волны, тогда как ПТФЭ и ПТФЭ/Cu материалы генерируют струю распыленных частиц. Установлено, что в головной части скорость струи частиц Сu наименьшая, глубина внедрения наибольшая, а размер отверстий наименьший, скорость струи частиц ПТФЭ наибольшая, глубина внедрения наименьшая, размер отверстий занимает среднее положение, скорость и глубина внедрения струи частиц ПТФЭ/Сu занимают среднее положение, тогда как отверстия имеют наибольший размер. Струя частиц ПТФЭ/Сu обладает более высокой эффективностью внедрения по сравнению со струей ПТФЭ, а ее проникающая способность выше, чем струи Cu. Облицювальний матеріал - один з ключових чинників при створенні бронебійних боєприпасів, який впливає на ефективність заглиблення. Працездатність кумулятивного заряду, який формується його облицюванням, визначається різними властивостями матеріалу в умовах вибухового навантаження, зокрема для мішені з елементами динамічного захисту, які зменшують проникаючу здатність, розсіюючи кумулятивний заряд. Вивчено робочі характеристики елементів кумулятивного заряду з різних матеріалів. Скінчнноелементне програмне забезпечення AUTODYN і метод гідродинаміки гладких частинок використовуються при моделюванні формування цих елементів і їх впровадженні в пластини-мішені з трьох матеріалів: Cu, ПТФЕ і ПТФЕ / Cu, що було перевірено експериментально. Показано, що кумулятивний заряд для мідного облицювання формується під дією детонаційної хвилі, тоді як ПТФЕ і ПТФЕ / Cu матеріали генерують струмінь розпорошених частинок. Встановлено, що в головній частині швидкість струменя частинок Cu найменша, глибина заглиблення найбільша, а розмір отворів менший, швидкість струменя частинок ПТФЕ найбільша, глибина заглиблення найменша, розмір отворів займає середнє положення, швидкість і глибина заглиблення струменя частинок ПТФЕ / Cu займають середнє положення, тоді як отвори мають найбільший розмір. Струмінь частинок ПТФЕ / Cu володіє більш високою ефективністю заглиблення в порівнянні зі струменем ПТФЕ, а її проникаюча здатність вище, ніж струменя Cu.